2014
DOI: 10.1371/journal.pone.0090779
|View full text |Cite
|
Sign up to set email alerts
|

How Do You Say ‘Hello’? Personality Impressions from Brief Novel Voices

Abstract: On hearing a novel voice, listeners readily form personality impressions of that speaker. Accurate or not, these impressions are known to affect subsequent interactions; yet the underlying psychological and acoustical bases remain poorly understood. Furthermore, hitherto studies have focussed on extended speech as opposed to analysing the instantaneous impressions we obtain from first experience. In this paper, through a mass online rating experiment, 320 participants rated 64 sub-second vocal utterances of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

49
435
8
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 286 publications
(500 citation statements)
references
References 101 publications
49
435
8
8
Order By: Relevance
“…Similarly, exploring the effect of seeking short-versus long-term relationships, Vukovic et al (2011) showed no significant preference in male pitch when female participants judged the voices for trustworthiness. However, McAleer et al (2014) found that high-pitched male voices were rated as more trustworthy compared with low-pitched voices. Considering trustworthiness in female voices, as is the case with dominance, there is a lack of studies, and again a lack of consistent findings.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, exploring the effect of seeking short-versus long-term relationships, Vukovic et al (2011) showed no significant preference in male pitch when female participants judged the voices for trustworthiness. However, McAleer et al (2014) found that high-pitched male voices were rated as more trustworthy compared with low-pitched voices. Considering trustworthiness in female voices, as is the case with dominance, there is a lack of studies, and again a lack of consistent findings.…”
mentioning
confidence: 88%
“…proposed for the importance of the eyes and mouth in establishing personality and emotion in faces (McAleer et al, 2014;Oosterhof & Todorov, 2008).…”
mentioning
confidence: 99%
“…As noted in the Introduction, these six dimensions were selected based on previous research on listener's perceptual evaluations of linguistic variables [18,29,30]. Each voice clip was played aloud once automatically, but participants were allowed to replay the clip as many times as they chose; in another survey variant, each clip was played only once and participants were unable to replay the clip.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, from a behavioral perspective, however, it has been repeatedly shown that the way one speaks reveals a lot about one's personality, level of confidence, as well as ethnicity, socio-economic circumstances, geographic background, sexuality, and ideological stance [8,[16][17][18]. The identification of African American speakers can be made even on the basis of the single word "hello" [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation